Cathemerality and Insensitivity to Predatory Fish Cues in Pond Isopods (Caecidotea communis) - Elizabeth C. Long; Erika V. Iyengar (Hydrobiology)
Because animals threatened by visually oriented predators may respond in sun-lit daytime but not at night, invertebrate responses to predatory challenges may yield varying results based on the time period within the 24 h daily cycle. We predicted that in laboratory experiments aquatic isopods exposed to kairomones from predatory fish would spend more time immobilized in daylight to avoid detection than those not exposed to kairomones but that this difference would disappear under the cover of nighttime darkness. We further predicted that isopods in the absence of kairomones would move at elevated rates in the daytime compared with night, seeking a precautionary proximity to shelters. However, contrary to our predictions, Caecidotea communis isopods exhibited consistent activity (movement rate and proportion of time spent moving) when exposed to kairomones or in the absence of such cues, at all of the three diurnal cycle periods examined. Thus, Caecidotea communis displayed cathemerality (sometimes called metaturnality), the first documented case of this behavior in crustaceans.